Concern about children and adolescents - Nairn, Agnes (Henry Stewart Talks, 2010)
How the commercial world can impact negatively on family relationships, Pester power, The effects of marketing on young people's friendships, Brand bullying, An overview of research on materialism and mental health, Inappropriate marketing, particularly sexual content on websites intended for young children, Unfair marketing, What children can and cannot understand, Rethinking unfair marketing following new research from neuroscience, How internet marketing is challenging the current rules of the game